Ethno Pedagogy Approach in Preparing Science Learning in The Society 5.0 Era - Sholeh Hidayat; Suroso Mukti Leksono; Ujang Jamaludin; Shintawati Shintawati (Jurnal Penelitian Pendidikan IPA, 2023)
This article is the result of a literature survey on Ethno pedagogy and education in the Society 5.0 era from various sources, including digital books, journal articles, and reports on the internet. In the field of education, Society 5.0 can utilize technology to provide more interactive and personalized learning, such as online learning or the use of Augmented Reality (AR) and Virtual Reality (VR) in learning. This era demands that education must be properly prepared to help individuals develop the skills and knowledge needed to face future challenges. The purpose of this paper is to examine more deeply the ethno-pedagogy approach and how this approach can be applied in preparing education in the Society 5.0 era. The culture-based educational approach is called Ethno pedagogy. The approach is very relevant in preparing education in the increasingly complex and diverse era of Society 5.0. This approach allows teachers to develop learning content that reflects students' cultural values. Technology can be a very useful tool in supporting an ethno-pedagogy approach